Client and staff perception toward federal welfare assistance delivery system at Welfare Department, Ministry Of Women, Family And Community Development / Nor Hayati Abdul Shukor... [et al.] - Abdul Shukor, Nor Hayati; Abu Hasan, Norraidah; Syed Mohd Fuzi, Sharifah Faatihah; Moulton, Noorie Haryaniee; Ahmad, Jasmine (2010)
Malaysia has made significant strides in reducing poverty by introducing initiatives which are intensive, prioritised and coordinated to achieve the National Key Result Areas (NKRA) target in improving living standard of citizen. The Ministry of Women, Family and Community Development is one of the main agencies responsible to improve the standard of living for low income household. One of the many efforts taken by the Ministry is to improve the Federal Welfare Assistance Delivery System. The main objective of the Federal Welfare Assistance Delivery System is to ensure all recipients receive the financial assistance within a specified time. This paper delves into the client and staff perception toward the implementation of Welfare Assistance Delivery System and the effectiveness of the system in distributing Federal financial welfare assistance on the first day of each month. Interview and survey were done to measure the level of employee awareness and views, as well as client satisfaction to this system. Findings of this research will contribute to the improvement of Welfare Delivery System at Welfare Department and other government agencies.